2010
DOI: 10.1177/0883073809348059
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydrocortisone on Neurodevelopmental Outcome in Premature Infants Less than 29 Weeks’ Gestation

Abstract: The use of postnatal dexamethasone in premature newborns can be associated with a deleterious neurodevelopmental outcome. The effect of hydrocortisone on developmental outcome in these patients is less clear. We therefore sought to examine the effect of hydrocortisone on early developmental outcome in premature newborns. We retrospectively examined the effect of hydrocortisone on developmental outcome during the first 2 years of life in premature infants <29 weeks' gestation at birth. Even though hydrocortison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
(17 reference statements)
0
16
0
Order By: Relevance
“…(16) However, when considering duration of therapy in a different cohort by 2 years, longer treatment with hydrocortisone (more than 7 days) was associated with worse developmental outcome. (21)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(16) However, when considering duration of therapy in a different cohort by 2 years, longer treatment with hydrocortisone (more than 7 days) was associated with worse developmental outcome. (21)…”
Section: Discussionmentioning
confidence: 99%
“…(13) However, such findings have not been clearly corroborated with hydrocortisone exposure. While one study raised concerns of motor and cognitive deficits in children with over a week of hydrocortisone therapy,(14) other studies have not reported abnormalities of brain development with hydrocortisone therapy in preterm newborns, resulting in their continued clinical use. (15, 16)…”
Section: Introductionmentioning
confidence: 99%
“…There are no published data about the long‐term effects of BTM, but we previously reported significant flow reduction in the anterior cerebral artery of preterm infants after BTM administration , which was not observed after HC administration . In comparison with untreated preterm infants, patients who have received HC do not present a higher rate of brain lesions or abnormal cognitive or motor development .…”
Section: Introductionmentioning
confidence: 93%
“…The z-score for body weight showed significantly greater loss in BTM group than HC group. untreated preterm infants, patients who have received HC do not present a higher rate of brain lesions or abnormal cognitive or motor development (8,(12)(13)(14)(15).…”
Section: Key Notesmentioning
confidence: 99%
“…Consequently, early physiological replacement of cortisol may be needed in extremely premature infants68). Retrospective studies and RCTs of early hydrocortisone replacement for CLD within the first week of life have been performed on the basis of this relative adrenal insufficiency69,70,71,72,73,74,75,76,77,78,79,80). Hydrocortisone is also being used increasingly for the treatment or prevention of vasopressor-resistant hypotension in extremely premature infants68).…”
Section: Clinical Evidence For Adverse Effects Of Postnatal Gcs On Thmentioning
confidence: 99%